1979
DOI: 10.1530/jrf.0.0550223
|View full text |Cite
|
Sign up to set email alerts
|

The role of the oviduct in reproduction; our knowledge and our ignorance

Abstract: Processes essential to reproduction known to occur in the oviducts of Eutherian mammals include sperm transport, capacitation, ovum pick-up and transport, fertilization and embryo transport and nourishment. Our knowledge of these processes in our own species, man, is incomplete. The reasons underlying our lack of information concerning the physiology of the human Fallopian tube are ethical, philosophical, and technical. Although some of our failure to obtain definitive data in women has been due to ethical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Until a few decades ago, the oviduct was considered as a simple passive conduit that provided an optimal microenvironment in terms of temperature, pH, osmotic pressure, nutrients, and oxygen pressure, enabling both R8 S Ghersevich and others the fertilization process and the early stages of embryo development (Pauerstein & Eddy 1979). The accumulated experimental evidence reviewed in the present work supports that the oviduct is actively involved in the reproductive process, considering that its secretion contains molecules capable of modulating gamete functions and interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Until a few decades ago, the oviduct was considered as a simple passive conduit that provided an optimal microenvironment in terms of temperature, pH, osmotic pressure, nutrients, and oxygen pressure, enabling both R8 S Ghersevich and others the fertilization process and the early stages of embryo development (Pauerstein & Eddy 1979). The accumulated experimental evidence reviewed in the present work supports that the oviduct is actively involved in the reproductive process, considering that its secretion contains molecules capable of modulating gamete functions and interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The fallopian tube appears to readily adapt to anatomical changes and restrictions [17]. It has been shown that even removal of segments of ampulla or the ampullary-isthmic junction in rabbits does not prevent fertility [19].…”
Section: Discussionmentioning
confidence: 99%
“…Fertility is unaltered after resection of the utero-isthmic junction or the ampullary-isth mic junction [8][9][10][11], which demonstrates that no essential sphincters exist on these sites. The isthmus itself appears to be re sponsible for the transistory retardation in ovum transport.…”
Section: Junctionsmentioning
confidence: 99%